THE EFFECTIVENESS OF THE TKA ONLINE APPLICATION PROCESS WITH THE VISA APPROVAL APPLICATION IN THE APPLICATION OF LIMITED STAY VISA APPROVAL FOR FOREIGN WORKERS - Mochamad Irsyad Makrufi (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
Manpower Being one of the aspects driving the open market economy, the entry of foreign workers into Indonesian territory is regulated in Indonesian government regulations. Use of visas and residence permits given to prospective foreign workers who will enter Indonesia through an online application submission process. However, in practice, the guarantor from foreign workers often encounter problems in the process of applying for a work visa for the Republic of Indonesia. Inhibiting factors in the process of applying for an RI work visa affect immigration services at the Visa Sub-Directorate.